Correlation of vascular stenosis with hemodialysis parameters in native arterio-venous fistula (AVF), pre and post percutaneous transluminal angioplasty (PTA) - Halim, Ani Darwina (2016)
Introduction: Stenosis and thrombosis of Arterio-Venous Fistula (AVF) has been an ongoing problem in hemodialysis patients. Early treatment by Percutaneous Transluminal Angioplasty (PTA) helps in maintaining AVF patency. However, how much PTA would improve the hemodialysis function was still questionable and only few literatures discussed on this matter. Hence, we performed a study on “Correlation of Vascular Stenosis with Hemodialysis Parameters in Native Arteriovenous Fistula (AVF), Pre and Post Percutaneous Transluminal Angioplasty”. Objective: To determine association between percentage of residual stenosis with hemodialysis success. Methodology: A total of 47 patients underwent Percutaneous Transluminal Angioplasty (PTA) in AMIEN Unit HUSM from June 2014 till October 2015; 14 were excluded and 19 lost to follow up leaving 14 subjects to study. All measurements of stenosis diameter were made from the PACS system whereas hemodialysis parameters were gathered through phone call to the subjects’ regular hemodialysis centre. Results: This study has revealed a weak correlation between percentage of stenosis with blood pump flow rate (Qb) in pre and post PTA. No correlation between percentage of stenosis with venous dialysis pressure (Vp) in pre and post PTA. The achieved technical success was 57.1% (P = 0.001). Conclusion: There is weak correlation between degree of stenosis with blood pump flow rate (Qb) but not observed in venous dialysis pressure (Vp).